1992
DOI: 10.1542/peds.89.5.895
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method of Estimating Cerebrospinal Fluid Pressure During Lumbar Puncture

Abstract: It is often difficult to measure cerebrospinal fluid (CSF) pressure in children. CSF flow through a spinal needle is described by the equation: Flow = pressure/(needle constant x relative viscosity). Thus, CSF flow rate during lumbar puncture can be used to estimate CSF pressure. Because the viscosity of CSF is approximately the same as that of normal saline, 0.9% NaCl was used to model CSF flow in vitro. Flow of saline through various spinal needles was measured as pressure and temperature were varied to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Even if the measurement of CSF opening pressure could be an important additional diagnostic factor, actually it is not routinely performed [ 18 ]. In our case, the neurosurgeon described the opening pressure as increased on both occasions by counting the number of CSF drops flowing through the spinal needle in a specified period, as already described [ 6 , 7 ], however we do not know the precise pressure measurement. In published studies on PTCS, CSF opening pressure was not documented for all the patients, because other factors documented indirectly elevated CSF pressure (symptoms, imaging data) [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Even if the measurement of CSF opening pressure could be an important additional diagnostic factor, actually it is not routinely performed [ 18 ]. In our case, the neurosurgeon described the opening pressure as increased on both occasions by counting the number of CSF drops flowing through the spinal needle in a specified period, as already described [ 6 , 7 ], however we do not know the precise pressure measurement. In published studies on PTCS, CSF opening pressure was not documented for all the patients, because other factors documented indirectly elevated CSF pressure (symptoms, imaging data) [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 78%
“…After the infant’s back was cleaned with antiseptic solution, 22-gauge spinal needle was inserted at the 4th lumbar space. In this case we had not the possibility to measure CSF opening pressure, anyway we used an empiric method already described in literature [ 6 , 7 ], and we observed that in 10 s the number of CSF drops flowing through the needle was higher compared to the number observed during routine procedure. After the needle was removed, the area was cleaned and a compressive medication on the needle site was performed.…”
Section: Case Presentationmentioning
confidence: 99%
“…Arguably, the presence of the CSF layer in spinal cord FE models is crucial to obtain accurate deformation of the spinal cord, with previous research in the brain demonstrating the importance of the CSF to accurately predict neural tissue deformation. 32 CSF has been reported to behave like a Newtonian fluid with mechanical properties similar to a saline solution containing 0.9% NaCl 33 and a reported density at 37 Celsius degrees ranging from 1.0003 to 1.0007 g/ml. 34 Previous computational studies investigating spinal cord compression demonstrated that FSI modeling of the CSF using the Arbitrary Lagrangian-Eulerian (ALE) numerical approach showed good correlation with reported experimental data.…”
Section: Spinal Cord Materials Models and Parametersmentioning
confidence: 99%
“…CSF has been reported to behave like a Newtonian fluid with mechanical properties similar to a saline solution containing 0.9% NaCl 33 and a reported density at 37° Celsius degrees ranging from 1.0003 to 1.0007 g/ml 34 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation